Contrarian ripple trading : - McNamara, Aidan J. (John Wiley & Son, 2008)
Written in a straightforward and accessible style, this reliable resource outlines the approach they've successfully used to capture profits from the stock market for many years. With this book as your guide, you'll quickly discover how you too can effectively implement a low-risk trading technique that consistently generates short-term profits on trades in large capitalization stocks--regardless of whether the market is moving up, down, or sideways.